2020
DOI: 10.3171/2020.5.focus20353
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of computer-assisted 3D navigation in multiple-level lateral lumbar interbody fusion in combination with posterior instrumentation for adult spinal deformity

Abstract: OBJECTIVEThe lateral lumbar interbody fusion (LLIF) technique is used to treat many common spinal degenerative pathologies including kyphoscoliosis. The use of spinal navigation for LLIF has not been broadly adopted, especially in adult spinal deformity. The purpose of this study was to evaluate the feasibility as well as the intraoperative and navigation-related complications of computer-assisted 3D navigation (CaN) during multiple-level LLIF for spinal deformity.METHODSRetrospective analysis of clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Studies have demonstrated that CAS navigation leads to substantially higher accuracy in pedicle screw insertion than free-hand and conventional two-dimensional fluoroscopy-guided methods [ 42 , 45 , 46 ]. Moreover, CAS technologies have been employed for cage insertion, resulting in improved performance [ 47 , 48 ]. This integration of CAS navigation holds promise for enhancing the precision and safety of spinal interventions [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that CAS navigation leads to substantially higher accuracy in pedicle screw insertion than free-hand and conventional two-dimensional fluoroscopy-guided methods [ 42 , 45 , 46 ]. Moreover, CAS technologies have been employed for cage insertion, resulting in improved performance [ 47 , 48 ]. This integration of CAS navigation holds promise for enhancing the precision and safety of spinal interventions [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…While current research has demonstrated positive clinical satisfaction and radiographic accuracy with the use of navigation for treating degenerative disease, literature on treating pediatric deformity with navigation is limited, particularly using large nationally represented cohorts. [ 11 12 ] Further, comparison of single-institution data to national-level database outcomes is also limited. Such comparison could provide insight into learning curves and technique-related factors associated with better outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Computer-assisted surgical (CAS) navigation techniques have been introduced as means to facilitate and standardize such interventions by providing 3D intraoperative spatial guidance and were shown to result in substantially higher pedicle screw-insertion accuracy compared to free-hand and conventional 2D fluoroscopy-guided methods [ 3 , 15 , 16 ]. Furthermore, CAS technologies have also been used for cage-insertion purposes [ 17 ] and have been shown to result in improved performance [ 18 ]. The most common CAS systems still rely on preoperative 3D imaging [ 19 ] and preoperative planning, which allows for the generation of patient-specific models (bio-mechanical digital twins), which can be used as the basis for computer simulations helping to determine and optimize surgery plans.…”
Section: Introductionmentioning
confidence: 99%